(3MGTjI GdHQeGhj Ydi TQM GdZGHIs - (3GdHQeGhj, EHQGgje Hf eMeO Hf TgGH GdOjf, J (B1106 (3g`s ((3MSjf Hf Ydj GdcQOj GdTGaYjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd GdJabg aj GdOjf Cge GdebUhOGJ GdYdeGA HGdJhajb ddNjQ hGdWGYGJ hNUge HGdeYQaI aj Yde Gdabg dCfg ef CYXe GdegeGJs
(3BNQgG (B:s
(3bhdg (B: (3hGdMeO ddg QH GdYGdejf (B: (3JbOe Ydjg GdcdGe aj GdNWHI hGddg SHMGfg hJYGdi CYde hfSCd Gddg GdcQje Cf jQTOfG Edi WQjb GdfLGM Efg aGdb GdMH hGdEUHGMs
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B1074 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 67s
(3eYLe GdeDdajf (B1 / 57s
(3EjVGM Gdecfhf (B2 / 136s
(3gOjI GdYGQajf (B1 / 36s
Keywords: (3Gdabg GdTGaYjs